New Face of European Union: Right-Wing Populism in the EU-Countries - E. V. Khakhalkina; K. P. Andreev; A. V. Munko (Vestnik MGIMO-Universiteta)
The European Union undergoes several qualitative transformations. Today it faces major demographic changes, the distance between the EU and national states is growing because of Brexit and high rates of immigration to Europe. The configuration of mainstream parties is also transforming in an unpredictable way. All these processes bring the phenomenon of right-wing populism to the forefront of political life of the European Union. This phenomenon was an answer both to internal andexternal challenges. The aim of the article is to identify the components of right-wing populism using the examples of some memberstates, to show its threats and risks, as well as ways to minimize the impact of this phenomenon on all aspects of the EU life. To achieve this goal, party programs (primarily right-wing populist ones), national and European elections data, materials from the Eurobarometer and other public opinion services, speeches and interviews of leading politicians, and other materials are used. The methodological approach is based on the principles of interdisciplinarity. The authors used comparative-typological, functional and structural methods. The problems of immigration and Islamophobia in the EU are explained with the help of the civilizational concept of A.J. Toynbee. The structure of the article provides the study of the phenomenon of right-wing populism through such indicators as separation of elites from the population (including European democracy and lack of democracy), immigration (and Islamophobia), as well as the EU identity. The article provides a detailed analysis of the member- state cases including the United Kingdom, Austria, Germany, Italy, France, Sweden, the countries of Eastern Europe and others. The authors conclude that right-wing populism has dual nature, its significance in individual countries of the European Union increases, and it is deeply integrated into the party and parliamentary mechanism of European democracies.